UPPER, AND THE STRUCTURE OF THE LOWER JAW, FEATURES ON THE FACE (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article explores the intricate features of the upper and lower jaw, shedding light on the underlying anatomy that defines the human face. Through a detailed literature analysis, we aim to uncover the structural components of these jaw regions and their implications for facial aesthetics and functionality. Employing a systematic approach, we delve into the methods used to study these features and present the results of our investigation. The discussion section critically examines the findings, drawing conclusions that contribute to our understanding of facial anatomy and offering suggestions for future research directions.